PENGARUH KECERDASAN VISUAL-SPASIAL TERHADAP HASIL BELAJAR MATEMATIKA DALAM PROBLEM BASED LEARNING PADA SISWA SMA KELAS X - Margareta Maya Sulistyarini; F. Gatot Iman Santoso (JIEM | JURNAL ILMIAH EDUKASI MATEMATIKA, 2015)
The purpose of this research is to know whether or not there was some  influence of visual-spatial intelligence on learning outcomes of Mathematics in Problem Based Learning of the Class X Students of Senior High School. This research is a Pre-Eksperiment Design quantitative research. The experiment was implemented to the second semester students of the academic year 2013/2014 of Senior High School 1 Widodaren, Ngawi with the class X as population. While, the sample of this research was the students of the class X of Natural Science 2, the class X of Natural Science 3, and the class X of Natural Science 4 with Problem Based Learning. The techniques of data collection used were test and non test (questionnaire). To obtain the sample, this research applied cluster random sampling technique. The instrument used in the test was a Mathematics outcomes test, whereas in the non test, visual-spatial intelligence questionnaires was applied. Mathematics outcomes test was used to determine the students’  ability in solving mathematic problems, whereas visual-spatial intelligence questionnaire was used to determine the level of the students’ visual-spatial intelligence. Both of research instruments were validated before trial. The result of the research showed that many students with high visual-spatial intelligence (n1) = 20 had average Mathematics learning outcomes () = 9.95 with a standard deviation of 15.0489. While, many students with low visual-spatial intelligence (n2) = 64, had average Mathematics learning outcomes () = 17.07 with a standard deviation of 20.6647. With t-test statistical analysis proved that there was no influence of visual-spatial intelligence on learning outcomes of Mathematics in Problem Based Learning (PBL) of the class X students of Senior High School.